USM RECEIVES COURTESY CALL FROM SAUDI ARABIA DELEGATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 21 January 2017 The Keeper of the Key to the Kaaba today led a fourman delegation from Saudi Arabia on a courtesy visit to Universiti Sains Malaysia (USM).